Assessing the Cervical Range of Motion in Infants With Positional Plagiocephaly. Issue 4 (June 2016) - Murgia, Massimiliano; Venditto, Teresa; Paoloni, Marco; Hodo, Brunilda; Alcuri, Rosaria; Bernetti, Andrea; Santilli, Valter; Mangone, Massimiliano
Abstract : Purpose: To determine if infants with positional plagiocephaly have limitations of active and passive cervical range of motion measured with simple and reliable methods. Methods: The examiners assessed bilateral active and passive cervical rotations and passive cervical lateral flexion. Cervical assessment was performed twice by 2 different physicians to assess intertester reliability. To assess intratester reliability the first investigator performed a second examination 48 hours after the first one. Results: One-hundred nine subjects were analyzed; 70.7% of the sample had head positional preference on the right, while 29.3% had head positional preference on the left ( χ 2 35.52, P  <0.001). Cervical rotations and lateral flexion showed reliable levels of agreement for intra and intertester reliability. Conclusions: The most limited range of motion in infants with positional plagiocephaly was cervical active rotation which affected more than 90% of patients. Passive cervical rotations and lateral flexion were limited in more than 60% of patients.